(untitled) (Research, Society and Development, 2020)
My experiences as a teacher in the English language area of ​​Basic Education motivated me to study Applied Linguistics (hereafter LA) and its focus on contemporary language teaching. The concern that has arisen about the need for language teaching to need cultural immersion for rapid and effective learning has led to the hypothesis that culturally contextualizing a student is to make them think the foreign language critically and consciously of the differences between this and your native language. In this perspective, the goal is to associate history and aesthetics with defining criteria of the way LA works and its orientation towards practical everyday problems related to language and communication. To this end, the study analyzes and develops the reading of a video clip in English from the point of view of contemporary life, compensating the object of study, the school, students and teachers in different contexts: body, ethnicity, nationality, gender, social class, among others, according to the texts studied. The research was carried out in a public school in the city of Cuiabá, with the participation of ninth grade students. The method of qualitative approach, in descriptive and bibliographic research based on the authors of the area of ​​Applied Linguistics, of cultural studies, in addition to the connection with the studies of reception theory, since musical groups are, in verbal expression, primarily in connotative language. It is expected that the study proposed here will culminate in a teaching that leads the student to think about another culture and, consequently, evolve with greater fluidity.